The Prediction of Wonogiri Dam’s Service Life Using Point Integrated Sampling - Abas Pamuji; Sobriyah Sobriyah; Cahyono Ikhsan (Institut Teknologi Sepuluh Nopember, 2017)
Sedimentation is the final process of erosion event due to run off, in which the soil grain is brought with through cavity, water channel toward the river then ends up in the reservoir. As a result, the reservoir will be filled in with sediment, so that the uncontrolled sediment will affect the reservoir’s service life. Point integrated sampling method is an alternative to find out the reservoir’s service life. The case study is conducted in multi-purpose Wonogiri reservoir, using the following instruments: GPS, dradloading set, meters, with maps from RBI and surfer software help to develop the sounding channel grids and to get the reservoir’s contour map. Point integrated sampling is a method of measuring the reservoir’s depth directly using dradloading with the large number of taking point with integrated sounding channel grids to obtain the elevation of sediment deposition currently. Then the data of reservoir’s elevation result was processed using surfer software. During running, it could be seen that the reservoir’s elevation increased compared with the original one during preparation because there is sediment deposition in the bottom of reservoir, so the reservoir’s sedimentation could make the reservoir’s dead storage full there by reducing the reservoir’s service life.